Functional capacity in patients with total hip arthroplasty: comparison of the Hardinge approach using the Trendelenburg test (CIPEEX, 2025)
This study reviews the functional capacity of patients undergoing total hip arthroplasty via different approaches, comparing the results with the Trendelenburg test. The narrative review used three articles that addressed anterolateral and posterior approaches. The results showed that the anterolateral approach preserves the gluteal muscles, while the posterior approach offers faster initial recovery. In the long term, both methods showed similar functional results. The conclusion highlights that the choice of technique should consider the patient's profile to optimize recovery and quality of life.
Keywords: Hip arthroplasty; Trendelenburg test; Functional capacity; Quality of life